Awareness-raising activities of advance care planning for community residents: a nationwide cross-sectional survey in Japan - Masayo Kashiwagi; Noriko Morioka; Miho Terajima; Kyoko Hanari; Takehiro Sugiyama; Ryota Inokuchi; Nanako Tamiya (BMC Palliative Care)
Abstract Background Japan is implementing awareness-raising of advance care planning for older adults; however, only 451 out of 1 741 municipalities were engaged in advance care planning awareness-raising activities among residents, according to a 2017 survey. This study examined advance care planning awareness-raising activities among community residents by local governments after the 2018 revision of the government guidelines, as well as utilization of the revised guidelines, issues in awareness-raising activities, and directions for future activities. Methods This cross-sectional questionnaire survey was conducted in prefectures and municipalities nationwide in 2022. Questions included the status, content, and issues of advance care planning awareness-raising activities for community residents. A multi-level logistic regression analysis was used to examine the characteristics of municipalities engaged in activities. Results Responses were received from 43 prefectures (response rate: 91.5%) and 912 municipalities (response rate: 53.1%). Of the municipalities, 63.6% (n = 580) reported “active” advance care planning awareness-raising. A high financial capability index and implementation of awareness-raising activities in the prefecture where the municipality was located were significantly associated with its awareness-raising activities. Municipalities engaged in awareness-raising activities reported experiencing issues related to the objectives, methods, and outcome evaluation of the activities. Conclusions Five-hundred eighty municipalities engaged in awareness-raising activities—a number that had increased significantly since the 2017 survey. Municipalities that could not engage in awareness-raising activities should receive financial support and other forms of support from prefectures. Furthermore, to ensure that municipalities clarify the purpose of awareness-raising and the desired outcomes, indices for quantitatively measuring results and achievements should be developed.